The Effectiveness of Snakes and Ladders Media on Sex Education for Children With Intellectual Disabilities - Trisni Handayani; Asep Supena; Rasmita Rasmita (Jurnal Inovasi Pendidikan Dasar, 2020)
Cases of sexual harassment and sexual deviations from year to year are increasing. Many factors cause it, including technological sophistication and ease of access, the existence of a family that does not care and a less sensitive educational environment. Parties who are victims of sexual harassment are usually women, especially children who experience intellectual disabilities. Nearly half of them have experienced 10 times the harassment. This study aims to determine the effectiveness of snakes and ladders media in improving understanding of sex education and preventing acts of sexual abuse and abuse in children who experience intellectual disabilities. This research uses descriptive qualitative method. Research subjects were students who experienced intellectual disabilities at Bekasi Jaya Extraordinary Elementary School. Data analysis was carried out through three main stages, namely reduction, data presentation, drawing conclusions. Snakes and ladders media is a game that uses symbols and images reinforced by verbal communication delivered by the teacher. The results showed that the use of snakes and ladders media effectively helped students who experienced intellectual barriers in understanding the messages contained in sex education content.